2019
DOI: 10.3390/ijerph16050825
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Fibrosis among World Trade Center Responders: Results from the WTC Health Registry Cohort

Abstract: Dust created by the collapse of the World Trade Center (WTC) towers on 9/11 included metals and toxicants that have been linked to an increased risk of pulmonary fibrosis (PF) in the literature. Little has been reported on PF among WTC responders. This report used self-reported physician diagnosis of PF with an unknown sub-type to explore the association between levels of WTC dust exposure and PF. We included 19,300 WTC responders, enrolled in the WTC Health Registry in 2003–2004, who were followed for 11 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Cohort studies after non-WTC exposures such as tobacco or asbestos raise serious concerns that twenty years after 9/11 incidence rates for interstitial lung diseases and lung cancer may rise to levels not seen in the general population. The WTC Health Registry has reported an increased incidence rate for self-reported interstitial lung disease in those with the highest WTC exposure history [82]. FDNY is currently involved in a CT imaging study to determine whether radiologic-confirmed interstitial disease is increased compared to the general population.…”
Section: Future Directions In Fdny Wtc Researchmentioning
confidence: 99%
“…Cohort studies after non-WTC exposures such as tobacco or asbestos raise serious concerns that twenty years after 9/11 incidence rates for interstitial lung diseases and lung cancer may rise to levels not seen in the general population. The WTC Health Registry has reported an increased incidence rate for self-reported interstitial lung disease in those with the highest WTC exposure history [82]. FDNY is currently involved in a CT imaging study to determine whether radiologic-confirmed interstitial disease is increased compared to the general population.…”
Section: Future Directions In Fdny Wtc Researchmentioning
confidence: 99%
“…As these patients had all worked as firefighters for years prior to their ILD diagnosis, this finding suggests a potential causal mechanism between firefighting and ILD. Pulmonary fibrosis in WTC first responders has been described, with an increasing incidence related to increasing levels of exposure following the attacks ( 6 ). Systematically derived occupational exposure histories are needed in this patient population in order to assess for both a dose-response relationship as well as high-risk activities leading to ILD in firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a wide variety of ILD subtypes in our firefighting cohort. Li and colleagues' description of pulmonary fibrosis in WTC first responders utilized patient self-report as a case definition, thus no determination of ILD subtype was able to be made ( 6 ). Sarcoidosis has been described in both WTC and non-WTC firefighters; however, this subgroup represented a small minority of ILD patients in our firefighting cohort ( 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…One recent report described potential work-related pleural abnormalities in 1453 WTC responders who were followed-up after a median of 6.8 years 116 . One recent study has reported that former WTC responders also developed pulmonary fibrosis and the adjusted hazard ratio was nearly 5-times higher in those with a very high level of exposure, and nearly 3-times higher in those with a medium level of dust exposure 121 . In addition to fibrotic changes, several former WTC dust-exposed workers were also reported to develop sarcoid-like granulomatous diseases 122 .…”
Section: Exposure To World Trade Centre (Wtc) Dustsmentioning
confidence: 99%